Considerações históricas e perspectivas atuais para o movimento indígena do complexo Macuxi-Wapixana - Lima, Jucilene Carneiro de (2018)
The dissertation addresses arguments and reflections on the organization of indigenous groups of lavrado (savanna area in Roraima) and how this organization suffers the effects of time and the influences of the surrounding society. Point of views, structural and functional, change course as new questions and desires are established. The premise of the study establishes that the present indigenous peoples' organization of lavrado had the directions changed from the process of colonization of Roraima, from the decades of 1800 on. The whole structure of the indigenous societies of lavrado was deeply changed, with the introduction of new values inherent to all cultural shock, and the introduction also of suffering and persecution caused by the Europeans, an unknown process by the indigenous, and saw colonization as an invasion to their territories, and also saw several massacres that resulted in extinction of peoples and much suffering. The resistance of the ethnic groups who survived, suffered various cultural losses and hardly managed to maintain and organize their culture without losing their identities, but they had their culture invaded. This is discussed in the present dissertation from past and present points of view, that will give the direction of the future, with arguments that bring discussion about indigenous and the colonization of Roraima, the resistance, the current perspectives. Within this context of the current perspectives, there is an activity that is conventionally called a "project", and the term makes the indigenous think about financial resources, what it is true, but the procedure ended up becoming institutionalized and to become a tool for non-indigenous presence in the communities. It is also mentioned within the current perspectives the beginning of a more ideological discussion, based on the last General Assembly of the Indigenous Peoples of Roraima, held in March 2018 at the Regional Center of Caracaranã Lake. In that Assembly, some leaders questioned the direction of indigenous movement in relation to the increasingly strong of non-indigenous ideas in the communities, which is against the ideas of the movement.